2019
DOI: 10.1111/ced.13930
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb cellulitis: low diagnostic accuracy and underdiagnosis of risk factors

Abstract: Accurate diagnosis and recognition of predisposing factors has been shown to be challenging in lower limb cellulitis (LLC). Assessment of 1746 consecutive patients with cellulitis presenting to a UK university hospital showed increasing overdiagnosis, with only 31.9% of patients referred during the period 2015-2018 having the diagnosis of LLC confirmed. Recognition of at least one predisposing factor increased from 61% to 89% following introduction of more specific screening questions. This identified a need f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Mistry et al 9 insisted that cellulitis was confirmed only in 31.9% of patients referred for suspicion of lower limb cellulitis in an English university center. Other diagnoses included venous eczema, chronic edema and lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…Mistry et al 9 insisted that cellulitis was confirmed only in 31.9% of patients referred for suspicion of lower limb cellulitis in an English university center. Other diagnoses included venous eczema, chronic edema and lymphedema.…”
Section: Discussionmentioning
confidence: 99%
“…No validated diagnostic criteria or tools exist,4 and up to 68% of people with suspected lower‐limb cellulitis (LLC) may not have the condition,5 leading to unnecessary hospital admission and antibiotic treatment 6. Painful red legs may also be caused by chronic conditions such as venous eczema and lymphoedema, which are unresponsive to antibiotics 5. This study investigated whether (i) a shorter duration of symptoms and (ii) a shorter duration of antibiotic treatment predicted whether referred patients had LLC.…”
Section: Figurementioning
confidence: 99%
“…6 Painful red legs may also be caused by chronic conditions such as venous eczema and lymphoedema, which are unresponsive to antibiotics. 5 This study investigated whether (i) a shorter duration of symptoms and (ii) a shorter duration of antibiotic treatment predicted whether referred patients had LLC. Diagnosis was defined clinically by experienced dermatologists.…”
mentioning
confidence: 99%
“…Patients should always be checked for tinea pedis, which should be treated with topical or systemic antifungals . Secondary cellulitis should be treated early with oral or intravenous penicillin V or flucloxacillin, or with clarithromycin if penicillin‐sensitive.…”
Section: Management Of Trench Foot: Vasodilators To Avoid Amputation?mentioning
confidence: 99%